Application of knowledge management tools: Comparative analysis of small, medium, and large enterprises - Natalia Sytnik (Nowy Sacz Business School National-Louis University, 2021)
PURPOSE: The purpose of this study was to conduct a comparative analysis of knowledge management (KM) initiatives in small, medium, and large enterprises operating in Ukraine, and to highlight the specific characteristics of KM policies, as well as the scope and intensity of KM tools application in these categories. In particular, the study focused on the consistency between the awareness of knowledge/KM importance and KM policies, and the scope and intensity of the application of both human-centered tools and information communication technology (ICT) tools. METHODOLOGY: The concept of the study was developed on the basis of an integrative socio-technical perspective. The empirical data were obtained through a questionnaire survey among 90 managers of small, medium, and large Ukrainian enterprises and were analyzed statistically. FINDINGS: Both common and distinctive characteristics of these categories in terms of KM were highlighted. Although all enterprises, regardless of their size, showed a high awareness of knowledge/KM importance for their business, significant distinctions between small and large enterprises were found with regard to their KM policies, the scope of advanced KM tools application, and the intensity of some traditional and advanced KM tools application. In all cases, large enterprises showed higher levels of these characteristics compared to small enterprises, whereas medium enterprises were more similar to large enterprises. In contrast to the common view on SMEs as a homogeneous sector in terms of KM, the study shows its heterogeneity in terms of KM initiatives. According to a number of indicators studied, significant differences were observed between small and large enterprises, whereas the distinctions between medium and large enterprises were much less obvious. IMPLICATIONS FOR THEORY AND PRACTICE: The theoretical contribution of this study was the provision of SMEs sector heterogeneity evidence based on a number of KМ characteristics. This finding allows us to deepen our knowledge of conceptual differences in KM approaches, applied by different enterprise categories. From a practical perspective, an enterprise size should be taken into account while designing specific KM policies, programs and tools to meet enterprises’ needs to a greater extent. The larger the enterprise is, the more structured, deliberate, and conscious the KM approach that should be applied is. ORIGINALITY AND VALUE: No empirical research that addresses the comparative analysis of KM initiatives in small, medium, and large enterprises operating in Ukraine, as well as in other transition economies of post-Soviet states, has been previously performed, and this study fills the gap.